HUBUNGAN KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN PUSKESMAS SUKABUMI KOTA PROBOLINGGO - Novi Sri Sandyawati (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2017)
This research was conducted by survey, the primary data collection method obtained directly from the original source, This research was conducted at Probolinggo Municipal Health Service, with the title